University: Steps of Growth - Ihor Tsependa (Vasyl Stefanyk Precarpathian National University, 2022)
The origins of Vasyl Stefanyk Precarpathian National University trace back to the Pedagogical Institute established in 1941 in Stanislav, which was the regional centre at that time. During the eighty years of its existence, the educational institution developed gradually: first it functioned as the Pedagogical Institute and its long-term existence was marked by numerous significant events, then it became a classical university, and, finally, it received the title and status of a national university. In recent years, the university has undergone radical changes in all areas of its life and work. There has come to the forefront the need of focusing on the experience of European universities while preserving national and state positions. Cooperation with leading European universities has made it possible to provide students with an opportunity to obtain a diploma not only from Vasyl Stefanyk Precarpathian National University, but also from one of the Polish ones. On the part of the staff the ongoing process of supporting the Ukrainian language as the state language goes hand in hand with general and persistent efforts teachers and students to master the English language. There have taken place significant changes in the organization of the educational process, introduction of new curricula, as well as modern teaching methods. Information technologies and the Internet have become an integral part of the educational process, while a powerful information center has been established to provide technical support for the training session organization and the online access to scientific sources. New ways of teaching presupposes the activation of the factor of students' individual work, which accounts for independent acquisition of a significant part of the necessary information.  The scientific library now has better possibilities to make scientific and educational literature essential for the training of highly qualified specialists available through the university website. The scientific activity of teachers has risen to a new level; new scientific centers have been created, new laboratories have been equipped; there is an ongoing international project aimed at restoration of the observatory on Mount Pip Ivan in the Carpathians. There has been a significant rise in scientific output measured by the Scopus scientific metric base; in recent years the number of doctors of science has increased by a third, and new promising scientific schools have been opened.  Several multivolume fundamental scientific works have seen the world. Student self-government has also intensified, cultural life is booming, there are significant achievements in sports. In the future, the university seeks to enter the top 100 best universities in the world.